Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/lm-03-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Influence of copyright exceptions and limitations on access to information in Kenya, Ghana and Uganda libraries

Abstract: PurposeCopyright exceptions promote access to information by users without breaching copyright. This research paper reviews copyright exceptions in Kenya, Ghana and Uganda and how they influence access to information in libraries. Objectives were to find out the implications of copyright exceptions in Kenya, Ghana and Uganda; advantages and disadvantages of copyright exceptions for libraries; and recommend best practices of copyright exceptions.Design/methodology/approachThis is a desktop research reviewing em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…‘neutral’), ‘agree’ or ‘strongly agree’ that there were exceptions and limitations in the copyright laws of Ghana. Though a number of the respondents ‘agree’ that the copyright laws of Ghana has exceptions and limitations ‘For the benefit of persons with disability’, Mungai et al (2020) have reported that the Copyright Act 690, 2005 of Ghana has no specific mention regarding copyright exceptions for people with disabilities. This clearly shows the ignorance of the respondents in this study of the law.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…‘neutral’), ‘agree’ or ‘strongly agree’ that there were exceptions and limitations in the copyright laws of Ghana. Though a number of the respondents ‘agree’ that the copyright laws of Ghana has exceptions and limitations ‘For the benefit of persons with disability’, Mungai et al (2020) have reported that the Copyright Act 690, 2005 of Ghana has no specific mention regarding copyright exceptions for people with disabilities. This clearly shows the ignorance of the respondents in this study of the law.…”
Section: Discussionmentioning
confidence: 99%
“…Though these exceptions vary from country to country, some common examples include reasonable copying for personal use, photocopying for archival purposes by libraries, quoting short passages of literary works for the purposes of criticism, and converting works into formats accessible by handicapped persons (Berkman Center for Internet and Society and EIFL, 2013; Mungai et al, 2020; Stokkmo, 2019). Other exceptions are broader, complex and ambiguous in their applications, such as the fair use doctrine of the United States and the fair dealing or fair practice doctrine employed in common law countries in some African countries such as Ghana (Adu and van der Walt, 2021a; Mungai et al, 2020; Samuelson, 2017; Stokkmo, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%